Genetic Algorithm-Based Optimal Protection Scheme for the Coordination of Bi-Directional Overcurrent Relays in a Carbon-Free AC Microgrid - Umbrin Sultana; Syeda Rimsha; Javed Rashid (Engineering proceedings, 2023)
With the increasing predilection for renewable energy sources across the world, the novel idea of a miniature version of a grid, called a microgrid, has emerged. The efficiency and sustainability of a power grid increase by integrating distributed energy resources (DERs). However, designing an optimum protection scheme has become a substantial challenge due to bi-directional power flows and varying fault levels in the microgrid with distributed energy resources (DERs). The existing protection strategies are not capable of dealing with the different operational states and natures of DERs. Therefore, modifications to the conventional protection schemes are required to benefit from the advantages of de-centralized power generation. Optimum co-ordination between the protection devices (PDs) is needed to achieve fast, secure, and reliable protection of the system. This paper proposes a protection philosophy for a renewable-based AC microgrid and validates its resilience by analyzing the response of the system in different faulty scenarios. Moreover, a genetic algorithm (GA) is used to optimize the proposed protection scheme to achieve a cost-effective, resilient, reliable, and long-term solution for sustainable power generation.